Potential of Zinc Oxide Nanostructures in Biosensor Application - Ibrahim M. Maafa (Biosensors)
The burgeoning field of biosensors has seen significant advancements with the induction of zinc oxide (ZnO) nanostructures, because of their unique structural, electrical, and optical properties. ZnO nanostructures provide numerous benefits for biosensor applications. Their superior electron mobility enables effective electron transfer between the bioreceptor and transducer, enhancing sensitivity and reducing detection limits. Furthermore, ZnO’s biocompatibility and non-toxicity make it ideal for in vivo applications, reducing the chances of adverse biological responses. This review paper explores the prospects of ZnO nanostructures in the development of biosensors, focusing on their morphological and structural characteristics. Various synthesis techniques, that include sol-gel, sputtering, and chemical vapor deposition, were successfully employed to prepare different ZnO nanostructures, like nanorods, nanotubes, and nanowires. The various findings in this field underscore the efficacy of ZnO nanostructures in enhancing the specificity and sensitivity of biosensors, presenting a promising avenue for the advancement of point-of-care diagnostic devices.